Role of the HIV-1 Reservoir to Maintain Viral Suppression in a Simplified Strategy for the Long-Term Management of HIV-1 Infection (The SIMPL’HIV Trial) - Branca, Mattia; Marinosci, Annalisa; Sculier, Delphine; Wandeler, Gilles; Yerly, Sabine; Stoeckle, Marcel; Bernasconi, Enos; Braun, Dominique L.; Neumann, Kathrin; Vernazza, Pietro; Cavassini, Matthias; Buzzi, Marta; et al. (Frontiers in Virology, 2022)
HIV-1 reservoir size and dynamics are promising parameters to ensure the safe prescription of simplified maintenance antiretroviral therapy in chronically HIV-1 infected patients. In the SIMPL’HIV trial, HIV-1 DNA was quantified in peripheral blood mononuclear cells obtained at baseline and week 48 to investigate changes over time and evidence of a predictive relationship to maintain HIV-1 RNA <20 copies/ml. Measurements were available for 175 patients, with no differences observed between treatment strategies. Findings showed that baseline HIV-1 DNA was lower in those with durable HIV-1 RNA <20 copies/ml compared with patients with incomplete viral suppression over 48 weeks.